Penggunaan E-Commerce dalam Upaya Meningkatkan Penjualan Produk UMKM Kerajinan Kulit Kerang Mutiara - Palembang, Citra Fathia; Permatasari Palembang, Septianti; Papilaya, Fioletta (Al-Khidmah Jurnal Pengabdian Masyarakat, 2024)
Nowadays, in the era of industrial revolution 4.0, the internet and digital technology have become basic necessities in facilitating people's activities in daily life such as going to school, working, selling, doing business and running a business. The increasing number of internet users in society provides opportunities for MSMEs to carry out their business activities and develop them more widely. Pearl Shell Craft MSME Raden Abdoellah is one of the MSMEs operating in the creative industry sector in Ambon City. The products produced are arts and crafts products such as displays/decorations, jewelry, etc. which are made from pearl shells. Products made apart from relying on orders from customers who come directly to buy at the production site, are only sold to shops/outlets of MSME partners located around the production site. The lack of information and insight regarding the use of e-commerce platforms also means that Raden Abdoellah MSME players are still limited in marketing their products. PkM activities at the Raden Abdoellah Pearl Shell Craft UMKM aim to provide information, insight and knowledge regarding the use of e-commerce to increase product sales capacity. PkM is implemented using lecture and mentoring methods in implementing one of the e-commerce platforms, namely Shopee, for MSME players. After implementing PkM activities, it is hoped that Raden Abdoellah MSME players can increase their knowledge and skills in marketing products online. In this way, broader consumer reach and increased product sales capacity will be achieved.